You are what you hear : how music and territory make us who we are - Witchel, Harry (Algora Pub., 2010)
Have you ever wondered why music makes you feel so good? Why did we evolve to have music, and what does music do to us? You Are What You Hear is a bit of a romp compared to the usual science book. Dr. Witchel, a specialist in music, pleasure and the brain, explains how the body and the brain are influenced by different kinds of music, why some music makes us joyous, while other music makes us sad, or angry, or anxious, and how the brain interprets this music. He also shows how music plays with your mind? what you think, how you decide what to buy, and even how smart you are. Dr. Witchel's int.